Ultrastructural organisation of the spermatozoon of Allopodocotyle tunisiensis Derbel and Neifar, 2009 (Digenea, Opecoelidae), an intestinal parasite of Solea aegyptiaca Chabanaud, 1927 (Teleostei, Soleidae). (April 2019) - Kacem, Hichem; Diagne, Papa Mbagnick; Miquel, Jordi
Highlights: Sperm characters are described for a second species of Allopodocotyle, A. tunisiensis . Ultrastructural organisation of the spermatozoon in opecoelids are analysed. Allopodocotyle spp. present a type IV of spermatozoon while the remaining opecoelids exhibit a type III. Abstract: The ultrastructure of the spermatozoon of Allopodocotyle tunisiensis (Digenea, Opecoelidae), an intestinal parasite of Solea aegyptiaca (Teleostei, Soleidae), is described by transmission electron microscopy (TEM). The mature spermatozoon is a filiform cell that exhibits two axonemes of different length with the 9+'1' pattern of trepaxonematan Platyhelminthes. In the anterior spermatozoon extremity, cortical microtubules are absent. They appear after the disappearance of an anterior electron-dense material, being initially in a continuous and submembranous layer. They surround only partially the sperm cell. Later, these cortical microtubules are distributed into two bundles. Additionally, the spermatozoon of A. tunisiensis shows two mitochondria, a nucleus, an external ornamentation of the plasma membrane, spine-like bodies, and a large amount of glycogen granules. According to the location of the external ornamentation, A. tunisiensis presents a Quilichini et al.'s type 2 spermatozoon. With respect to the posterior extremity, the sperm cell of A. tunisiensis corresponds to the Quilichini et al.'s opecoelid type. The morphology of the first mitochondrion with a U-shaped posterior extremity is described for the first time in a digenean spermatozoon.